2019
DOI: 10.1002/ajb2.1388
|View full text |Cite
|
Sign up to set email alerts
|

Parallel increases in insect herbivory and defenses with increasing elevation for both saplings and adult trees of oak (Quercus) species

Abstract: Herbivory is predicted to increase toward warmer and more stable climates found at lower elevations, and this increase should select for higher plant defenses. Still, a number of recent studies have reported either no evidence of such gradients or reverse patterns. One source of inconsistency may be that plant ontogenetic variation is usually not accounted for and may influence levels of plant defenses and herbivory. METHODS:We tested for elevational gradients in insect leaf herbivory and leaf traits putativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 43 publications
3
7
0
Order By: Relevance
“…Q. canariensis , Q. pyrenaica , Q. suber ) moved to cluster A as adults, suggesting that while syndromes remain consistent across ontogenetic stages, there are underlying shifts in trait expression at the intra‐specific level which deserve attention (Figure 3). Accordingly, this finding also implies changes in the magnitude of expression of individual traits for which we have found evidence in our previous work with oaks (Galmán, Abdala‐Roberts, Covelo, Rasmann, & Moreira, 2019; Moreira et al, 2017) and, to a lesser extent, in the present study. Therefore, parallel assessments of ontogenetic changes in individual traits (i.e.…”
Section: Discussionsupporting
confidence: 88%
“…Q. canariensis , Q. pyrenaica , Q. suber ) moved to cluster A as adults, suggesting that while syndromes remain consistent across ontogenetic stages, there are underlying shifts in trait expression at the intra‐specific level which deserve attention (Figure 3). Accordingly, this finding also implies changes in the magnitude of expression of individual traits for which we have found evidence in our previous work with oaks (Galmán, Abdala‐Roberts, Covelo, Rasmann, & Moreira, 2019; Moreira et al, 2017) and, to a lesser extent, in the present study. Therefore, parallel assessments of ontogenetic changes in individual traits (i.e.…”
Section: Discussionsupporting
confidence: 88%
“…The elevational changes in anti‐herbivory defenses differ among plant species (Moreira et al, 2018), and the previous studies documented almost all possible associations between herbivory and plant physical and chemical defenses along elevational gradients. These included a simultaneous decrease in both herbivory and plant defense (Pellissier et al, 2014), a decrease in herbivory accompanied by an increase in plant defenses (Rasmann et al, 2014) and, finally, simultaneous increases in both insect herbivory and anti‐herbivore defense from low to high elevations (Abdala‐Roberts et al, 2016; Galmán et al, 2019). Our results are in line with the last pattern because the increase in herbivory with elevation occurs despite the decrease in SLA.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are in line with the last pattern because the increase in herbivory with elevation occurs despite the decrease in SLA. SLA, which reflects leaf physical properties, is often interpreted as physical antiherbivore defense (Barton & Koricheva, 2010; Galmán et al, 2019; Kergunteuil et al, 2018; Wilson et al, 1999). Furthermore, SLA correlates with other leaf traits (e.g., with foliar nitrogen) that influence plant quality for herbivores (Reich et al, 1999), and therefore the decrease in SLA with elevation observed in our study (and in several previous studies: Descombres et al, 2020; Galmán et al, 2019; Garibaldi et al, 2011) likely indicates the decrease in plant quality.…”
Section: Discussionmentioning
confidence: 99%
“…Inducible defenses may be under greater species‐specific selective pressures and are more likely to be adaptive (Baldwin, 1999; Koricheva et al., 2004; Moreira et al., 2018). Understanding the costs of defense production in both constitutive and inducible defenses is essential to understanding the evolution of plant defenses (Galman et al., 2019a; Galman et al., 2019b; Martinez‐Swatson et al., 2020). We found that herbivore damage induced a greater aRGR (apical relative growth rate), greater production of condensed tannins and alterations in leaf aspect and leaf ratio, as well as induced non‐structural carbohydrate re‐allocation to root storage.…”
Section: Discussionmentioning
confidence: 99%